Determination of Heavy Metal Levels in Fishes from the Lower Reach of the Kelantan River, Kelantan, Malaysia - Rohasliney Hashim; Tan Han Song; Noor Zuhartini Md Muslim; Tan Peck Yen (Tropical Life Sciences Research, 2014)
This study aimed to assess the concentrations of cadmium (Cd), nickel (Ni) and lead (Pb) in the tissues of fish collected from the lower reach of the Kelantan River, Malaysia. Fishes were collected using gill nets during the dry and wet seasons. A total of 78 individual fish were caught and comprised 6 families, 11 genera and 13 species. The dorsal muscle was analysed using a graphite furnace Atomic Absorption Spectrometer (AAS). The mean concentration of Cd in Chitala chitala (0.076 mg/kg) was above the critical limit values of the European Commission (EC), World Health Organization (WHO) and Food and Agriculture Organization (FAO). The mean concentrations of Cd in Barbonymus gonionatus and Tachysurus maculatus were already at the level of concern, whereas the other species were approaching the limits of permissible levels. No fish samples were found to have a Ni level higher than the permissible limit of 0.5–0.6 mg/kg set by the WHO (1985). Osteochilus hasseltii (0.169 mg/kg) and T. maculatus (0.156 mg/kg) showed high Pb concentrations. The concentrations of heavy metals were found to be elevated in the wet season (p<0.05). Omnivorous fish were detected with elevated concentrations of Cd and Ni, whereas carnivorous fish had the highest concentration of Pb. The concentrations of Cd and Pb in fish tissues were positively correlated with fish weight (p<0.05). This study determined that the fish species caught in the Kelantan River were contaminated with non-essential metals (Cd, Ni and Pb). Nevertheless, the heavy metal concentration in the fish tissues, with the exception of C. chitala, O. hasseltii and T. maculatus, did not exceed the EC, FAO, Malaysian Food Act (MFA) or WHO guidelines. Satu kajian untuk menentukan tahap kandungan logam berat [kadmium (Cd), nikel (Ni) dan plumbum (Pb)] dalam tisu ikan telah dijalankan di Sungai Kelantan. Pensampelan ikan dilakukan pada musim kering dan basah menggunakan pukat. Enam famili, 11 genus dan 13 spesies daripada 78 ekor ikan dapat ditangkap. Tisu ikan tersebut dianalisa menggunakan relau grafit Spektrofotometer Serapan Atom (AAS). Kepekatan Cd dalam Chitala chitala (0.076 mg/kg) didapati melebihi nilai had kritikal European Commission (EC), World Health Organization (WHO) dan Food and Agriculture Organization (FAO). Kepekatan Cd dalam Barbonymus gonionatus dan Tachysurus maculatus pula didapati telah menghampiri nilai had yang ditetapkan. Kesemua spesies ikan yang diperolehi didapati tidak mengandungi kepekatan Ni yang melebihi had yang ditetapkan oleh WHO (1985) iaitu 0.5–0.6 mg/kg. Osteochilus hasseltii (0.169 mg/kg) dan T. maculatus (0.156 mg/kg) mempunyai nilai kepekatan Pb yang tinggi berbanding spesies lain. Tahap kandungan logam berat didapati lebih tinggi pada musim basah berbanding musim kering (p<0.05). Ikan omnivor telah dikesan dengan kepekatan tinggi Cd dan Ni, manakala ikan karnivor mempunyai kepekatan Pb tertinggi. Kepekatan Cd dan Pb dalam tisu ikan berkorelasi secara positif dengan berat ikan (p<0.05). Oleh itu, kajian ini menunjukkan bahawa spesies ikan yang ditangkap di Sungai Kelantan tercemar dengan logam berat. Walau bagaimanapun, kepekatan logam berat dalam tisu ikan tidak melebihi garis panduan EC, FAO, Malaysian Food Act (MFA) dan WHO kecuali C. chitala, O. hasseltii and T. maculatus yang telah menghampiri atau mencecah nilai had kritikal.